Induced fit in arginine kinase. - Zhou, G (2000)
Creatine kinase (CK) and arginine kinase (AK) are related enzymes that reversibly transfer a phosphoryl group between a guanidino compound and ADP. In the buffering of ATP energy levels, they are central to energy metabolism and have been paradigms of classical enzymology. Comparison of the open substrate-free structure of CK and the closed substrate-bound structure of AK reveals differences that are consistent with prior biophysical evidence of substrate-induced conformational changes. Large and small domains undergo a hinged 13 degrees rotation. Several loops become ordered and adopt different positions in the presence of substrate, including one (residues 309-319) that moves 15 A to fold over the substrates. The conformational changes appear to be necessary in aligning the two substrates for catalysis, in configuring the active site only when productive phosphoryl transfer is possible, and excluding water from the active site to avoid wasteful ATP hydrolysis.